Controlling Quantum Cascade Laser Optical Frequency Combs through Microwave Injection (Laser Photonics Rev. 15(12)/2021). Issue 12 (10th December 2021) - Schneider, Barbara; Kapsalidis, Filippos; Bertrand, Mathieu; Singleton, Matthew; Hillbrand, Johannes; Beck, Mattias; Faist, Jérôme
Abstract : Quantum Cascade lasers In article number 2100242, Barbara Schneider and co‐workers present strong microwave injection in quantum cascade laser frequency combs as a means for controlling the lasing state. Varying modulation frequency and power enables us to broaden and shift the spectral output as well as modify the phase profile. Moreover, the fast gain dynamics enable rapid switching between separate spectral regions with just a single device.